2006
DOI: 10.1080/10494820600852969
|View full text |Cite
|
Sign up to set email alerts
|

Peer coaching with interactive wireless technology between student teachers: Satisfaction with role and communication

Abstract: In technology-savvy Singapore, wireless communication devices were used over four weekly lessons to facilitate communication between pairs of student teachers (STs). In the naturalistic setting of a neighbourhood primary school, one ST used the technology to coach the other who was engaged in teaching. (Both were familiar with the lesson plan and in a later lesson the roles were reversed.) The coach's comments (tape recorded) to the teacher were guided by lecturer-designed focus sheets. Following each lesson, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
5
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…However, even with these feasibility challenges, EC teachers perceived that BIE peer coaching increased the quality of their teaching and improved children’s communication. Our results were consistent with those obtained in other BIE studies in which researchers implemented the coaching with EC teachers (e.g., Ottley et al, 2015) and teachers implemented the intervention with their co-teachers (Fry & Hin, 2006; Scheeler et al, 2010). Even so, given the diversity in EC classrooms, future researchers should examine methods to improve the feasibility of BIE coaching to aid in the ease of its use among other EC teacher dyads.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…However, even with these feasibility challenges, EC teachers perceived that BIE peer coaching increased the quality of their teaching and improved children’s communication. Our results were consistent with those obtained in other BIE studies in which researchers implemented the coaching with EC teachers (e.g., Ottley et al, 2015) and teachers implemented the intervention with their co-teachers (Fry & Hin, 2006; Scheeler et al, 2010). Even so, given the diversity in EC classrooms, future researchers should examine methods to improve the feasibility of BIE coaching to aid in the ease of its use among other EC teacher dyads.…”
Section: Discussionsupporting
confidence: 91%
“…One specific type of coaching with great potential to reduce the research-to-practice gap is peer coaching, which is defined as teachers observing one another and providing reciprocal feedback with the goal of enhancing instruction (Scheeler, Congdon, & Stansbery, 2010). Peer coaching has benefits over other types of coaching, such as assisting teachers in overcoming barriers associated with assignments in their respective professional roles, being contextually relevant, and receiving feedback from someone with whom teachers have rapport and a positive relationship (Fry & Hin, 2006; Scheeler et al, 2010). Importantly, peer coaching has positively affected teachers’ content knowledge, problem-solving skills, teaching techniques, and self-efficacy (e.g., Jang, 2010; Latz, Speirs Neumeister, Adams, & Pierce, 2009; Slater & Simmons, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Participants indicated that their candidate peers could help assist candidates to complete clinical requirements of online preparation programs, such as recording their teaching video for them, providing technical assistance so the candidate can focus on working with P-12 students during the observation, and offering performance-based feedback to their peer. Some research shows that peer coaching has benefits over coaching provided by experts, supervisors, and administrators because peers already have rapport and they have a stronger understanding of the classroom setting (Fry & Hin, 2006). Our previous research (Ottley, Coogle, Rahn, & Spear, 2017) and that of other scholars (e.g., Jang, 2010;Scheeler, Congdon, & Stansbery, 2010) has shown peer coaching to be an effective approach to supporting teachers in using evidence-based practices.…”
Section: Delivering Performance-based Feedbackmentioning
confidence: 79%
“…Focus group (qual) Survey (quant) and focus group (qual) Fry and Hin (2006) Singapore 21 student teachers coaching mixed methods 4 Survey (quant) Goos and Bennison (2008) Australia 19 student teachers collaboration qualitative 6 9…”
Section: Disclosure Statementmentioning
confidence: 99%